Exploring the Psychological Trauma of Mary Turner in Doris Lessing’s The Grass Is Singing - Ahmed, Sheikh Saifullah (IUBAT Review, 2023)
This paper explores the traumas of Mary Turner, the protagonist of the widely celebrated novel The Grass Is Singing (1950) by Doris May Lessing (1919-2013). The plot of the novel centers on Mary Turner, a white farmer’s wife whose declining mental health and eventual tragedy reveal society’s deeply established biases and repressive structures. Psychological trauma includes abuse, violence, accidents, war, and witnessing traumatic occurrences that may cause long-term mental health issues such as flashbacks, nightmares, anxiety, despair, emotional numbness, and relationship issues. Therefore, using trauma theory and psychological frameworks, the study examines Mary’s traumatic experiences that shape her actions and interactions throughout the novel. In the novel, Mary seems to be terrified by her infantile memories, traumatized by the social slurs, and trapped in an African parched terrain, approximating the wasteland, from which she cannot escape. She has relentless nightmares about haunting sexuality, sporadically with her father or Moses. It seems that her repressed desires unlocked into her dreams persecute her inexorably. Therefore, she mislays control over herself and suffers from a complete nervous breakdown. Consequently, Mary undergoes a syndrome of psychopathology that includes neurosis, psychosis, paranoia, and personality disorder for which she cannot lead a normal life. A qualitative content analysis method is adopted to inspect Mary’s childhood trauma that persuades her disorders. The analysis suggests a correlation between adolescent trauma and psychosis, which can disrupt an individual’s sense of self, conduct, and mental state. Accordingly, Mary’s conscious control breaks down as her childhood pain returns, revealing her natural urges and unconscious side. IUBAT Review, 6(2): 115-130